Increasing reproducibility in preclinical stroke research: the correlation of immunofluorescence intensity measurements and Western blot analyses strongly depends on antibody clonality and tissue pre-treatment in a mouse model of focal cerebral ischemia - Prehn, Anna; Hobusch, Constance; Härtig, Wolfgang; Michalski, Dominik; Krueger, Martin; Flachmeyer, Bianca (Frontiers in Cellular Neuroscience, 2023)
In the setting of stroke, ischemia not only impairs neuronal function, but also detrimentally affects the different components of the neurovascular unit, which are shown to be involved in the transition from reversible to long-lasting tissue damage. In this context, the glial proteins myelin basic protein (MBP) and the 2',3'-cyclic-nucleotide 3'-phosphodiesterase (CNP) as well as the vasculature-associated basement membrane proteins laminin and collagen IV have been identified as ischemia-sensitive elements. However, available data from immunofluorescence and Western blot analyses are often found to be contradictory, which renders interpretation of the respective data rather difficult. Therefore, the present study investigates the impact of tissue pretreatment and antibody clonality on immunofluorescence measurements of the mentioned proteins in a highly reproducible model of permanent middle cerebral artery occlusion. Here, immunofluorescence labeling using polyclonal antibodies revealed an increased immunofluorescence intensity of MBP, CNP, laminin and collagen IV in ischemic areas, although Western blot analyses did not reveal increased protein levels. Importantly, contrary to polyclonal antibodies, monoclonal ones did not provide increased fluorescence intensities in ischemic areas. Further, we were able to demonstrate that different ways of tissue pretreatment including paraformaldehyde fixation and antigen retrieval may not only impact on fluorescence intensity measurements in general, but rather one-sidedly affect either ischemic or unaffected tissue. Therefore, immunofluorescence intensity measurements do not necessarily correlate with the actual protein levels, especially in ischemia-affected tissue and should always be complemented by different techniques to enhance reproducibility and to hopefully overcome the translational roadblock from bench to bedside.